Planetary Praxis & Pedagogy
X, 150 p.
Keywords: “Good books make important points because their authors have something worthwhile to say. This book is more than a good book because its authors not only make important points but they do so in ways that exemplify the transdisciplinarity the authors write about. In eight interesting and insightful chapters the book connects pedagogy, marketing, development, immanence, race, resilience, technology, and the commons in ways that show the necessity and importance of transdisciplinary thinking. This is a book for those who seek deeper and more creative connections to a sustainable way of life, a way of life that opens up imaginative acts of hope.” – John Novak, Professor in the Department of Graduate and Undergraduate Studies in Education at Brock University; his research interests include: Philosophy of education, Invitational theory and practice, Educational leadership, and Social-cultural contexts of education .